2017
DOI: 10.1002/jat.3471
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the silica-induced molecular events in lung epithelial cells using the RNA-Seq approach

Abstract: Silicosis is a prolonged, irreversible and incurable occupational disease, and there is a significant number of newly diagnosed cases every year in Hong Kong. Due to the long latency of the disease, the diagnosis can be missed until detailed clinical examination at a later stage. For a better control of this deadly disease, detailing the pro-inflammatory and fibrotic events in the macrophage would be instrumental in understanding the pathogenesis of the disease and essential for the significant biomarkers disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
3
10
1
Order By: Relevance
“…The overall comparison with previous report in a silicosis mice model (Chen J. et al, 2018) using CAT curves showed that very few genes (Supplementary Figure 1A) or pathways (Supplementary Figure 1B) showed consistency with our findings. Specifically, some relevant genes revealed by previous research did not show significant alterations in our results, such as the genes Ccl2 and Ccr2, which have been validated in mice silicosis models (Chen J. et al, 2018), and the DNA-binding protein inhibitor (ID) family genes, which were found to be relevant in the early responses of silicosis in epithelial cells (Chan et al, 2017). Considering differences between species and the focus of some previous research on early disease stages, our study conducted in human lungs improves our understanding of the true disease state and in particular the molecular changes underpinning silicosis.…”
Section: Discussioncontrasting
confidence: 45%
“…The overall comparison with previous report in a silicosis mice model (Chen J. et al, 2018) using CAT curves showed that very few genes (Supplementary Figure 1A) or pathways (Supplementary Figure 1B) showed consistency with our findings. Specifically, some relevant genes revealed by previous research did not show significant alterations in our results, such as the genes Ccl2 and Ccr2, which have been validated in mice silicosis models (Chen J. et al, 2018), and the DNA-binding protein inhibitor (ID) family genes, which were found to be relevant in the early responses of silicosis in epithelial cells (Chan et al, 2017). Considering differences between species and the focus of some previous research on early disease stages, our study conducted in human lungs improves our understanding of the true disease state and in particular the molecular changes underpinning silicosis.…”
Section: Discussioncontrasting
confidence: 45%
“…Therefore, transcriptional evaluations focused on silicosis were performed in various silica‐ or asbestos‐treated pulmonary cells. RNA‐Seq transcriptome analysis on silica‐treated A549 lung epithelial cells suggested that genes in the immune response and inflammatory pathways were altered by silica exposure (Chan et al, ). In silica‐treated A549 cells, DEGs involved a number of DNA binding inhibitors, transcriptional factors, growth factors, caveolin 1, cadherin 1 and many more.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analyses investigating the effects of crystalline silica on human bronchial epithelial cells (BEAS 2B and NHBE) provided insightful profiles of differentially expressed cytokines and chemokines (Helmig, Dopp, Wenzel, Walter, & Schneider, 2013;Perkins et al, 2012). RNA-Seq transcriptome analysis evaluating molecular events in A549 lung epithelia cells showed that crystalline silica exposure altered the expression of genes responsible for immune response and inflammation (Chan et al, 2017). Apart from epithelial cells, alveolar macrophages were also shown to be susceptible to silica exposure, which was able to trigger the activation of multiple transcription factors and cytokines (Leung et al, 2012;Melaiu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al [ 38 ] used RNA sequencing to evaluate the inflammatory and fibrotic effects of cultured A549 cells in vitro, exposed to CS up to a limit of 20% cytotoxicity. CS was 99% pure (Sigma, USA) and in the 0.5-10 μm size range.…”
Section: Methodsmentioning
confidence: 99%